Meta Analysis: Effect of Waiting Time and Outpatient’s Satisfaction in Hospitals - Safitri, Feby; Murti, Bhisma; Ichsan, Burhannudin (Journal of Health Policy and Management, 2024)
Background: Service waiting time is one of the problems that causes patient complaints in several hospitals. The length of patient waiting time reflects how the hospital manages service components that are tailored to the patient's situation and expectations, as well as analyzing the effect of waiting time on the level of outpatient patient satisfaction at the hospital. The purpose of this study was to determine the effect of waiting time on the satisfaction level of outpatients at the hospital. Subjects and Method: A systematic review and meta-analysis was performed using the PRISMA guidelines and the PICO model including Population = Outpatients; Intervention = short waiting time < 2 hours; Comparison = long waiting time > 2 hours; Outcome = satisfaction. Articles are collected from databases such as PubMed, Science Direct, and Google Schoolar. The keywords used in the database search were "waiting time and satisfaction" OR "satisfaction" AND "outpatient" AND "hospital' AND "cross-sectional study". A total of 9 articles met the inclusion criteria, namely primary full text paper, cross-sectional study design, with a relationship size adjusted Odds Ratio (aOR), outpatient study subjects, interventions in the form of short waiting times < 2 hours and outcomes in the form of outpatient satisfaction for meta-analyses were then assessed using RevMan 5.3. Results: The meta-analysis which is dominated by Ethiopia shows that there is an effect of waiting time on patient satisfaction. Patients who receive services with short waiting times <2 hours have the possibility to be satisfied 6.86 times compared to long waiting times > 2 hours (aOR= 6.86; 95% CI= 1.31 to 3.26; p= 0.002) Heterogeneity (I2 = 83%) -> using random effects with statistically significant results. Conclusion: Patients who wait for a short time have the possibility to be satisfied 6.86 times compared to long waiting times. Keywords: waiting time, satisfaction, outpatien, hospital. Correspondence: Feby Safitri. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: safitri.feby@gmail.com. Mobile: +6282143749717.